Efficiency measurements in the QinetiQ Turbine Test Facility with temperature distortion and swirl: the mass flow rate measurement problem - Beard, PF; Povey, T (Measuring Techniques in Turbomachinery, 2008)
This work describes the development and implementation of a system to perform accurate measurements of mass flow rate in the Turbine Test Facility (TTF) at QinetiQ Farnborough. The facility has recently been upgraded so that turbine aerodynamic efficiency measurements can be performed and the implementation of a system for mass flow rate measurement formed part of that upgrade. The measurement system is novel in that accurate measurements can be performed with both combustor representative turbine inlet temperature distortion (hot-streaks) and swirl. The TTF is a short-duration (approximately 0.5 second run time) isentropic light piston turbine facility, which has been used for aerodynamic and heat transfer investigations of – primarily – high-pressure turbine stages, although it has also been configured to operate as a 1½ stage (HP stage with IP or LP vane) turbine. The MT1 turbine is a highly loaded unshrouded design relevant to modern military engine design, or future civil engine design. The turbine is engine scale, and all relevant dimensional parameters for aerodynamics and heat transfer are matched: Re, M, N T01 , Tgas Twall . Hot streaks are simulated in the TTF by the controlled mixing of hot and cold gas streams. The cold stream is introduced though a conventional sonic metering nozzle, from a large reservoir acting in blow-down mode. In a transient facility, the accurate measurement of stage mass flow rate with combustor representative inlet temperature distortion and swirl presents an interesting problem, as the capacity of the ngv row is affected by both of these combustor representative inlet flow-fields. In the TTF, a mass flow rate measurement system has been developed using the exit contraction of the piston tube as a subsonic converging-diverging venturi: upstream and , and throat are measured at a number of circumferential locations around the exit contraction to determine the mass flow rate of the hot stream. The effective area of the venturi was measured using a novel blow-down calibration technique which is described. 0 p T0 p The bias error in the measurement of mass flow rate with and without temperature distortion was 1.37 per cent and 1.13 per cent respectively, of the same order as the accuracy associated with conventional tertiary devices. The precision uncertainty was 0.198 per cent in both cases. Accuracy is unaffected by the introduction of inlet swirl.